2008
DOI: 10.1007/s00335-008-9101-5
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of disease-associated DNA polymorphisms in the genes of cattle, goat, sheep, and pig

Abstract: Genetic variations through their effects on gene expression and protein function underlie disease susceptibility in farm animal species. The variations are in the form of single nucleotide polymorphisms, deletions/insertions of nucleotides or whole genes, gene or whole chromosomal rearrangements, gene duplications, and copy number polymorphisms or variants. They exert varying degrees of effects on gene action, such as substitution of an amino acid for another, shift in reading frame and premature termination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 336 publications
(242 reference statements)
0
26
0
5
Order By: Relevance
“…Several genome-scan studies have identified quantitative trait loci and several molecular markers, such as single nucleotide polymorphisms (SNPs), that are related to mastitis, suggesting that resistance to the condition has a significant genetic component despite its low heritability (Klungland et al, 2001;Heringstad et al, 2003;Holmberg and Andersson-Eklund, 2004;Khatkar et al, 2004;Ogorevc et al, 2009). Indeed, some studies have demonstrated variations or polymorphisms in genes related to immune response that could be associated with mastitis resistance (Detilleux, 2002;Ibeagha-Awemu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several genome-scan studies have identified quantitative trait loci and several molecular markers, such as single nucleotide polymorphisms (SNPs), that are related to mastitis, suggesting that resistance to the condition has a significant genetic component despite its low heritability (Klungland et al, 2001;Heringstad et al, 2003;Holmberg and Andersson-Eklund, 2004;Khatkar et al, 2004;Ogorevc et al, 2009). Indeed, some studies have demonstrated variations or polymorphisms in genes related to immune response that could be associated with mastitis resistance (Detilleux, 2002;Ibeagha-Awemu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…También subrayan la importancia de estudios poblacionales previos a la implementación de selección asistida por marcadores. Estos estudios, junto con el análisis de la validez de los marcadores en los distintos sistemas de producción, son fundamentales para determinar el alcance y eficacia de posibles planes de mejora genética que utilicen marcadores moleculares (Ibeagha-Awemu et al, 2008;Neuner et al, 2009). El análisis fenotípico y de otros marcadores relacionados con la calidad de la carne en estas poblaciones permitirá evaluar el potencial productivo del bovino Criollo Uruguayo y sus cruzas, en el marco de la caracterización y conservación de los recursos genéticos animales mundiales.…”
Section: Discussionunclassified
“…Unfortunately, causal mutations have been identified only for a few Mendelian genetic disorders (Table 3, [117][118][119][120][121]). …”
Section: Genetic Determinants Of Disease Susceptibilitymentioning
confidence: 99%